2014
DOI: 10.5114/cipp.2013.40636
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental traits as predictors of effectiveness of psychotherapy (prolonged exposure) for PTSD in a group of motor vehicle accident survivors

Abstract: backgroundThe aim of the study was to analyze demographic (age, gender and education), temperamental (briskness and emotional reactivity) and psychopathological (severity of the disorder, comorbid symptoms of personality disorders) predictors of effectiveness of psychotherapy (Prolonged Exposure; PE) of posttraumatic stress disorder (PTSD). It was expected that temperamental traits -briskness (BR) and emotional reactivity (ER) (involved in arousing and change of PTSD symptoms) -would predict the post-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(21 reference statements)
0
8
0
3
Order By: Relevance
“…Basing the recruitment decisions on temperament profiles which are less prone to develop PTSD symptoms may result in fewer psychological and psychiatric problems among people at a higher risk of trauma exposure. Popiel and Zawadzki (2013) also revealed that prolonged-exposure trauma-focused psychotherapy (one of the most effective therapies of PTSD; see the last comparison done by Haagen, Smid, Knipscheer, & Kleber, 2015) is less effective among people high on emotional reactivity when they are provided with the therapy after more than 1 year since trauma exposure. More research may provide us with valuable information which would help to provide people with a therapy best adjusted to their possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basing the recruitment decisions on temperament profiles which are less prone to develop PTSD symptoms may result in fewer psychological and psychiatric problems among people at a higher risk of trauma exposure. Popiel and Zawadzki (2013) also revealed that prolonged-exposure trauma-focused psychotherapy (one of the most effective therapies of PTSD; see the last comparison done by Haagen, Smid, Knipscheer, & Kleber, 2015) is less effective among people high on emotional reactivity when they are provided with the therapy after more than 1 year since trauma exposure. More research may provide us with valuable information which would help to provide people with a therapy best adjusted to their possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The latter programs are not yet advanced or widely used, the effective ones have been already introduced, for example, among Israeli students (Wolmer, Hamiel, & Laor, 2011) or policemen (Arnetz, Nevedal, Lumley, Backman, & Lublin, 2009; see Skeffington, Rees, & Kane, 2013, for the summary). As temperament traits are considered one of the most important moderators of the relationship between extreme stress and psychopathology (Strelau, 2008) and there are first reports they may also moderate symptom reduction (Popiel & Zawadzki, 2013), the need for further research in the area seems to be incontestable. At the same time, the lack of a meta-analysis of the relationship between personality and temperament traits with PTSD symptoms is apparent.…”
mentioning
confidence: 99%
“…The examination of the relationship between trauma response and temperament may provide important benefits in determining the recruitment of people at high risk of exposure to trauma and in adjusting the appropriate therapy process for those exposed to trauma especially when trauma-focused therapies are considered ineffective in people with high emotional reactivity. Determining the decisions in job recruitment or distribution of duties according to the temperament profiles of individuals will reduce the development of psychiatric problems (55,58).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of specific mediators of the relationship between personality/temperament and well-being that can be influenced by psychological interventions would be valuable because this would give an opportunity to tailor these interventions to one’s temperamental preferences and further check the usefulness of such an approach. Relatively few studies suggest that temperament may be perceived as a significant moderator of therapy effectiveness (An et al, 2012; Balestri et al, 2019; Kampman & Poutanen, 2011; Mouren & Gorwood, 2010; Popiel & Zawadzki, 2013; Purper-Ouakil et al, 2010; Tomita et al, 2014), however still the research on mediators is lacking.…”
Section: Hypothesesmentioning
confidence: 99%
“…Temperament, as defined by RTT, determines an individual’s external stimulation processing capability and preferred ways of stimulation regulation, increasing the risk of the development of dysfunctional behaviors and/or psychopathological symptoms. It was found to be a risk factor of the development of somatic symptoms (Fruehstorfer et al, 2012), obesity (Oniszczenko et al, 2015), depression (Hintsa et al, 2016), autism (Pisula et al, 2015), posttraumatic stress disorder (Cyniak-Cieciura & Zawadzki, 2021), personality disorders (Zawadzki et al, 2012) and alcohol abuse (Miklewska & Miklewska, 2000), and moderated the effects of cognitive-behavioral therapy of PTSD (Popiel & Zawadzki, 2013).…”
Section: Hypothesesmentioning
confidence: 99%